HIV-1 sequence data coverage in Central East Africa from 1959 to 2013 - Lamers, S; Barbier, A; Ratmann, O; Fraser, C; Rose, R; Laeyendecker, O; Grabowski, M (Mary Ann Liebert, 2016)
Central and Eastern African HIV sequence data have been most critical in understanding the establishment and evolution of the global HIV pandemic. Here we report on the extent of publicly available HIV genetic sequence data in the Los Alamos National Laboratory Sequence Database sampled from 1959 to 2013 from six African countries: Uganda, Kenya, Tanzania, Burundi, the Democratic Republic of Congo, and Rwanda. We have summarized these data, including HIV subtypes, the years sampled, and the genomic regions sequenced. We also provide curated alignments for this important geographic area in five HIV genomic regions with substantial coverage.